Democracy, Nazi trials, and transitional justice in Germany, 1945-1950 - Pendas, Devin O. 1966- (Cambridge University Press, 2020)
"This book is a history of transitional justice in occupied Germany. The book offers a new way of looking at the role of law in political transitions. Scholars and activists have long argued that prosecuting past atrocities promotes democracy in the wake of dictatorship. This view is, at best, overly simplistic. The two Germanys started in more or less the same place, politically speaking. Both practiced transitional justice extensively. Yet the results were diametrically opposed: democracy in the West, dictatorship in the East. Transitional justice does not necessarily produce only one kind of political outcome. It can be democratizing but it can also help build authoritarianism. The book shows how Nazi trials were "better" in the East than in the West, in that there were more of them, with more stringent sentences, and a more adequate theory of justice. Yet the eastern trials helped the new Stalinist dictatorship's claim to legitimacy. In the West, judges and lawyers defended Nazis in the name of liberal rights and the rule of law. This got Nazis off the hook, but it also promoted democracy. The politics of transitional justice can be paradoxical, creating unintended consequences and surprising outcomes"--